Nasional Sharia Commercial Bank Transformation Base on Most Dominant Agreement: Sale and Purchase Contract (Murabaha) - Suharto, Babun (Journal of Islamic Economics Perspectives, 2019)
The purpose of this study proved and tested to what extent sharia banks in Indonesia remain consistent in carrying out their role as one of the financial institutions that accordance with shariah compliance. One of the product is channeling financing with profit-sharing systems. To identify these problems, this research adopted associative quantitative analysis and used panel data regression analysis techniques with E-Views 9. Secondary data were obtained from the annual Report the 12 National Sharia Bank from 2015 to 2017 period. This investigation concluded that there was a significant effect of Murabaha contract financing on profitability. However, Istishna, Mudharaba, and Musyaraka contracts have no significant influence on profitability partially. The study result has demonstrated that even though the sharia banks have been running a business in Indonesia for 27 years, up to now they have not optimized the transaction agreement based on profit-loss sharing.